Students - Teachers Communication Patterns in Islamic Elementary Schools: Analyzing the Hierarchical Context of Standpoint’s Theory - Eti Nurhayati; Yayah Nurhidayah (Al Ibtida: Jurnal Pendidikan Guru MI, 2022)
AbstractThis study aims to identify the patterns of student-teacher communication in learning as perceived by teachers from the perspective of Standpoint Theory. This descriptive research uses questionnaires distributed to teachers. The results of this research show that first, the most dominant attitude in student communication is the desire to always please the teacher; second, the most common language use in student communication is frequent complaints; third, the most dominant verbal communication style of students is always speaking politely; fourth, the most prevalent nonverbal communication style is frequent eye contact, active listening, and silence; and fifth, the most dominant personality attitude in student communication is a lack of willingness to make sacrifices. These findings indicate that student-teacher communication remains hierarchical. Teachers are perceived to have more power compared to students, maintaining the stigma of teachers as figures to be "obeyed and emulated." This results in students being more passive, hesitant to take initiative, dependent, and primarily focused on pleasing the teacher.Keywords: students-teachers communication pattern, Islamic elementary school, Standpoint theory. AbstrakPenelitian ini bertujuan untuk mengetahui pola komunikasi siswa-guru dalam pembelajaran yang dipersepsi oleh guru ditinjau dari teori Standpoint. Penelitian ini bersifat deskriptif dengan menggunakan kuesioner yang kepada guru. Hasil penelitian ini menunjukkan bahwa pertama, sikap dalam berkomunikasi siswa yang paling dominan adalah selalu ingin menyenangkan guru; kedua, penggunaan bahasa dalam komunikasi siswa yang paling dominan adalah sering komplain; ketiga, gaya komunikasi verbal siswa yang paling dominan adalah selalu berbicara sopan; keempat, gaya komunikasi nonverbal siswa yang paling dominan adalah sering melakukan kontak mata, lebih banyak mendengar, dan diam; dan kelima, sikap kepribadiaan siswa dalam berkomunikasi yang paling dominan adalah jarang mau berkorban. Temuan ini menunjukkan bahwa komunikasi guru-siswa masih bersifat hierarkis. Guru dianggap memiliki kekuasaan lebih besar dibandingkan siswa, sehingga stigma guru masih dipertahankan sebagai figur yang harus "dipatuhi dan ditiru". Hal ini mengakibatkan siswa menjadi lebih pasif, ragu untuk mengambil inisiatif, tergantung, dan lebih berfokus untuk menyenangkan guru.Kata kunci: pola komunikasi siswa-guru, sekolah dasar Islam, teori Standpoint.